FINANCIAL SELF-EFFICACY TERHADAP FINANCIAL MANAGEMENT BEHAVIOR PADA GENERASI MILENIAL KOTA DENPASAR - Ayu Indira Dewiningrat; Made Ratih Nurmalasari; Putu Putri Prawitasari; Ni Putu Ari Krismajayanti; I Wayan Aditya Tariana (JUIMA : JURNAL ILMU MANAJEMEN, 2023)
The aim of this research is to determine the influence of financial literacy, love of money, and locus of control on financial management behavior, and to see whether financial self-efficiency can moderate this relationship. The population used in this research is the Millennial Generation who live in Denpasar City which cannot be determined. Purposive sampling is used to obtain respondents with certain criteria. There were 19 indicators used in this research with a total of 104 research subjects who met the sample criteria to be used. The data analysis technique used is Moderated Regression Analysis (MRA) with SPSS 24.0 for Windows. This research found that financial literacy and love of money are determinants of financial management behavior. Financial management behavior is influenced by financial literacy and love of money. In this context, these two factors enable the millennial generation in Denpasar City to carry out financial management behavior armed with their literacy and love of money. This research also found that financial self-efficacy strengthens and weakens the relationship between financial literacy and love of money, respectively. It is known that financial self-efficacy, in this context is a person's self-confidence in managing their finances well, can be the basis for strengthening and weakening the financial management behavior of the Denpasar City millennial generation.